2023
DOI: 10.21831/cp.v42i1.52231
|View full text |Cite
|
Sign up to set email alerts
|

Development of the play-based model on volley ball basic techniques for junior high school

Abstract: This study aims to develop a play-based learning model for basic volleyball techniques and to assess the effectiveness of the volleyball basic technique learning through the approach in improving the learning outcomes on volleyball subject in the juniour high school. The research type was research and development which adopted the 10-step theory of Borg and Gall.. This study used both qualitative and quantitative data analysis. The study designed employed a pretest-posttest control group design to determine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…The students' results can be assessed by their ability to pass tests (Mardiana et al, 2023). Moreover, students' problem-solving skills are associated with applying knowledge acquired to new situations through analysis and evaluation (Samsudin et al, 2023). This shows that teachers and students participate in the education process by focusing on fulfilling the curriculum designed for a specific subject.…”
Section: Introductionmentioning
confidence: 99%
“…The students' results can be assessed by their ability to pass tests (Mardiana et al, 2023). Moreover, students' problem-solving skills are associated with applying knowledge acquired to new situations through analysis and evaluation (Samsudin et al, 2023). This shows that teachers and students participate in the education process by focusing on fulfilling the curriculum designed for a specific subject.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research related to learning models in physical education for students with special needs has been widely carried out. The integration of Augmented Reality (AR) in physical education learning simplifies the comprehension of teaching materials for both teachers and disabled students, rendering the educational experience more engaging (Widyaningsih et al, 2023).Previous research regarding the development of a volleyball learning model for school students can show that the learning model used is effective in increasing student interest (Megawati et al, 2023).The volleyball learning model centered around gameplay proves to be more effective in enhancing the fundamental volleyball skills of junior high school students (Samsudin et al, 2023). Previous research found that the learning model was effectively applied to basketball learning for children with disabilities (Pressé et al, 2011).…”
Section: Introductionmentioning
confidence: 99%